PENENTUAN JUMLAH MOL UDARA DALAM SELINDER DAN BOLA MENGGUNAKAN HUKUM BOYLE-MARIOTTE - SOUISA, MATHEUS (PATTIMURA UNIVERSITY, 2011)
Has done research on different container and the syringe bulb to determine the number of moles of air. If the gas or air is introduced into the syringe or bulb then the more air is forced into it. The analysis uses Boyle-Mariotte law shows that the number of moles of air in the syringe with constant temperature and number of moles of air at constant volume is a sphere with eqqual 0.02 mol. Thus two different media (cylindrical and spherical), giving the same number of moles. Obtaining the number of moles show that the application of Boyle-Mariotte is derived from the ideal gas law is appropriate.